A Review on Automatic Tyre Pressure Control Technologies and Solar as Possible Energy Solution - Amosun, Taiwo Semiu; Anisiji, Obiora Emeka (Borobudur Engineering Review, 2024)
Tyre inflation pressure plays a crucial role in ensuring safe and economical driving. Automatic tyre inflation systems are designed to constantly maintain tyre pressure at the proper level. Different techniques exist to monitor, control and maintain tyre inflation pressure. Systems currently in development for tyre pressure control include dual tyre pressure equalizers, automatic tyre inflation system, central tyre inflation system as well as others which are in the prototype stage. In dual tyre pressure equalizer systems, a single sensor unit is mounted to the vehicle wheel end, monitoring the pressure in both tyres of a dual-tyre assembly, with a hose connection to each tyre valve stem. If pressure levels between the tyres do not match, either due to temperature warming of one tyre position versus the other, unequal loading, or slow air seepage, the system will attempt to bring the inflation pressure of the two tyres to the same level. Automatic tyre inflation systems monitor tyre inflation pressure relative to a pre-set target and re-inflate tyres whenever the detected pressure is below the target level. In central tyre inflation system, the driver can select the target pressure from an in-cab display, in order to raise or lower the tyre inflation level depending on the operating conditions of the vehicle. One of the greatest challenges in designing a tyre pressure control system is providing the required energy to power the system. This paper reviews some state-of-the-art tyre pressure control technologies. Then possibility of solar energy-powered solution reviewed. The proposed solar energy solution is for land vehicles used especially in arid region of the world.